2010
DOI: 10.1159/000274468
|View full text |Cite
|
Sign up to set email alerts
|

Are Sodium Transporters in Urinary Exosomes Reliable Markers of Tubular Sodium Reabsorption in Hypertensive Patients?

Abstract: absorption and urinary exosomal excretion of sodium transporters, and (2) the profile of sodium transporter excretion related to blood pressure (BP) changes with salt intake. A 24-hour ambulatory BP monitoring and a 24-hour urine collection were performed after 1 week on a low-and 1 week on a high-salt diet. Results: Animal studies: urinary NKCC2 and NCC excretion rates correlated well with their abundance in the kidney. Human studies: 6 patients (15%) were classified as salt sensitive. The NKCC2 and NCC abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…Of interest, the increase in NCC in urinary exosomes we observed in this study with a low-sodium diet was similar to the increase Esteva-Font et al found for NCC in a separate study. 10 Our study suggests that pNCC was better than prostasin as a marker of aldosteronism, which could be explained by several factors. First, although prostasin is sensitive to aldosterone and can activate ENaC, this does not necessarily render it a direct marker of ENaC activity and, as such, it may not be a direct marker of distal sodium reabsorption.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Of interest, the increase in NCC in urinary exosomes we observed in this study with a low-sodium diet was similar to the increase Esteva-Font et al found for NCC in a separate study. 10 Our study suggests that pNCC was better than prostasin as a marker of aldosteronism, which could be explained by several factors. First, although prostasin is sensitive to aldosterone and can activate ENaC, this does not necessarily render it a direct marker of ENaC activity and, as such, it may not be a direct marker of distal sodium reabsorption.…”
Section: Discussionmentioning
confidence: 66%
“…Esteva-Font et al, however, found no difference in the abundance of NCC in urinary exosomes of patients with salt-sensitive hypertension. 10 Recently, it has become clear that the phosphorylated form of NCC (pNCC) represents the active form of NCC and that trafficking and phosphorylation of NCC can be regulated independently.…”
mentioning
confidence: 99%
“…In another human study 41 patients with mild-moderate hypertension underwent 1 week of low and then 1 week of a high sodium diet [217]. 24 hour sodium excretion was 44mmol/24h at the end of the low sodium diet and 162mmol/24h at the end of the high sodium diet respectively.…”
Section: Human Evidencementioning
confidence: 99%
“…In a 2008 paper they used this new technique of urinary exosome analysis with western blot to quantify NCC expression in 8 subjects with FHHT and 8 family member controls, finding that expression of NCC was approximately 4 fold higher in FHHT subjects than related controls [187]. Other groups have used exosome analysis to quantify NCC expression in response to high and low salt diets [217], and in limited fashion pNCC in patients with primary aldosteronism [216]. A recent study looked at NCC and NKCC2 expression in patients with Gitelman and Bartter syndrome [228].…”
Section: What Are Urinary Exosomes and How Do We Isolate Them?mentioning
confidence: 99%
See 1 more Smart Citation